Faktor-Faktor Yang Berhubungan Dengan Praktik Personal Hygiene Saat Menstruasi Pada Remaja Putri Pondok Pesantren Al Asror Kota Semarang Tahun 2019 - Anna Himmatin Nisa; Dharminto Dharminto; Sri Winarni; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Personal hygiene practices during menstruation become an important issue especially for adolescent girls who live in pesantren. The life of girls in pesantren is different from girls in general. Adolescent girls must adapt to the density of pesantren activities and regulations. In addition, there is still little discussion of reproductive health in pesantren. The purpose of this study was to determine the factors that associated with personal hygiene practices during menstruation in girls Al Asror Islamic Boarding School in Semarang. This research is a quantitative research with explanatory research method and cross-sectional study design. The population in this study was 133 girls with a sample of 108 girls taken using simple random sampling technique. The results showed that majority of respondents were in the age group of 14-16 years (63%) and the majority used disposable sanitary napkins (90.7%). Correlation test results show there is a significant relationship between the use of infrastructure (p-value = 0.031, r = 0.207) and friend support (p-value = 0.005, rho = 0.271) with personal hygiene practices during menstruation in girls. Variable beliefs about menstrual myths and the amount of information media are not related to personal hygiene practices during menstruation in girls. Girls stay with friends in one room to allow a level of intimacy to trust to share experiences, share information, and advise one another on personal hygiene during menstruation. It is recommended for girls to filter information obtained from peers so that they are not wrong in receiving information.